Penerapan Sistem Informasi Manajemen Untuk Meningkatkan Efektivitas Operasional Perusahaan - Turyanigsih, Turyanigsih; Yunita Azizzah; Dewi Mas Arumsari; itra Anisa Tika Putri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study discusses the application of Management Information Systems (MIS) to improve the operational effectiveness of companies. The purpose of this article is to analyze how MIS supports decision-making and operational processes. The research method used is descriptive qualitative by reviewing relevant literature. The findings show that MIS helps streamline data processing, enhance communication, and improve strategic planning. In conclusion, effective MIS implementation significantly contributes to increasing company efficiency and competitiveness.